Conservation Status of the Amphibians of Malaysia and Singapore - Das, Indraneil; Norsham, Yaakob; Jeet, Sukumaran; Tzi, Ming Leong (Natural History Publications (Borneo) Sdn. Bhd, 2014)
Malaysia and Singapore are two independent countries in southeastern Asia (Fig. 1), situated north of the equator, and enjoying mostly tropical climate (with a hint of seasonality in the north). One part of the former (Peninsular Malaysia) stretches from the southern border of Thailand southward to the narrow Johor Strait that separates it from the island state of Singapore. A second, insular, part of Malaysia lies across the South China Sea on the northern coast of Borneo (see below). Malaysia has a total land area of 328,657 km2 , far exceeding the land area of Singapore (700 km2 ). The term ‘Malay Peninsula’ here will refer to Peninsular Malaysia and Singapore, ‘Malaysia’ to the Malaysian Federation, comprising Peninsular Malaysia, Sabah, Sarawak, and Labuan. The geological history of the landmass has been described by Hutchison and Tan (2009); also see Wong (2011) for a recent synthesis of the biological (including palaeontological) and physical characteristics of the southeastern Asian region as a whole.